Comparative feeding value of forages from two cereal-legume based cropping systems for beef production from crossbred (Bos taurus X Bos indicus) steers and subsequent performance of underfed and realimented steers - Umunna, N.N.; Osuji, P.O.; Khalili, H.; Nsahlai, I.V.; Crosse, S. (Cambridge University Press, 1995)
Foods produced from two cereal-legume cropping systems were evaluated in a 250-day growth trial using Friesian X Boran crossbred steers. Crops and crop combinations in cropping system 1 were oat-vetch (Avena sativa-Vicia dasycarpa; OV), wheat-trifolium (Triticum aestivum-Trifolium steudneri; WT), teff (Eragrostis tef) and chickpea (Pisum sp). Cropping system 2 differed from 1 in that maize-lablab (Zea mays-Lablab purpureus; ML) replaced wheat-trifolium. Twenty-four steers (mean initial live weight 157 (s.d. = 4.5) kg were assigned randomly within weight group to four treatments. Treatments comprised ad libitum teff straw (TS) given alone (T1), TS plus wheat middlings (WM) given at 0.01 M (body weight (T2), forages from system 1 fed in the order OV, WT and TS plus chickpea for 135, 48 and 67 days respectively (T3) or forages from system 2 fed in the order OV, ML and TS plus chickpea for 73, 147 and 30 days respectively (T4). The feeding period for each crop of T3 and T4 was based on its contribution to the total dry matter (DM) yield of the cropping system. Apparent digestibility of DM measured by the acid-insoluble ash method was higher (P<0.05) for T3 and T4 than for T2. DM intake was higher (P<0.01) than those on T2 resulting in 1 kg higher daily intake of digestible DM than for T3 and T4. Steers on T4 gain per kg food) followed a similar trend as ADG) more (P<0.01) weight than steers on T3 (149 85 g per head per day) but less (P<0.01) than those T2 (528 g per head per day). Steers on T1 lost 94 g per head per day. Food efficiency (kg gain per kg food) followed a similar trend as ADG. At the end of the trial, two steers from each treatment were slaughtered for carcass assessment and the remaining steers used in a realimentation study of 120 days and then slaughtered for carcass. Steers which gained poorly during the 250 day trial (T1, T3 and T4) exhibited compensatory gains of 497, 550 and 565 g per head per day respectively compared with 398 g per head per day for steers on T2. Carcasses from T2 yielded significantly more (P<0.05) lean and fat than carcasses from T3 and T4. The results suggest that growing food crops in association with legumes has the potential of increasing cattle performance.